Empowering Women through Majelis ta’lim: Social Change in Al-Hasanah Community - fauzi wirahyuda; Abdullah (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This article discusses the dynamics of the Al-Hasanah Islamic Religious Learning Council (Majelis ta’lim Al-Hasanah) as a religious learning space that plays a vital role in fostering social change among mothers. Using a descriptive qualitative approach, this research examines the activity patterns, social interactions, and the impact of the council on increasing religious knowledge, forming moral values, and strengthening community solidarity. The study results indicate that the Al-Hasanah Islamic Religious Learning Council (Majelis ta’lim Al-Hasanah) functions not only as a means of religious instruction but also as a forum for empowerment that influences the mothers' thinking, attitudes, and social behavior. The resulting social change is evident in the increased participation of women in religious activities, the formation of stronger social networks, and the emergence of a collective awareness to develop more religious and harmonious lifestyles. Thus, the Islamic Religious Learning Council (Majelis ta’lim) plays a strategic role not only in shaping religious identity and strengthening social cohesion at the community level, but also in illustrating women’s religious agency in contemporary Muslim societies, where informal religious spaces function as sites of empowerment, negotiation of gender roles, and reinterpretation of Islamic values in line with broader discussions on Islamic feminism and modern religious subjectivity.